2016
DOI: 10.1371/journal.pone.0155871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fibre (Pectin) and/or Increased Protein (Casein or Pea) on Satiety, Body Weight, Adiposity and Caecal Fermentation in High Fat Diet-Induced Obese Rats

Abstract: Dietary constituents that suppress appetite, such as dietary fibre and protein, may aid weight loss in obesity. The soluble fermentable dietary fibre pectin promotes satiety and decreases adiposity in diet-induced obese rats but effects of increased protein are unknown. Adult diet-induced obese rats reared on high fat diet (45% energy from fat) were given experimental diets ad libitum for 4 weeks (n = 8/group): high fat control, high fat with high protein (40% energy) as casein or pea protein, or these diets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 52 publications
3
44
1
2
Order By: Relevance
“…FOS and inulin-type fructans have been reported to increase SCFA production, increase GLP-1 production, and decrease energy intake in rodent models, on adding these oligosaccharides in the diet at around 5-10% (wt/wt). [5][6][7][8][9][30][31][32] The dose of FOS at 3% in the present study seems insufficient to exert an anorexic effect in the diet-induced obesity model. In contrast, DFA III at 3% in the diet is effective in preventing excess energy intake.…”
Section: After 2 Weekscontrasting
confidence: 60%
“…FOS and inulin-type fructans have been reported to increase SCFA production, increase GLP-1 production, and decrease energy intake in rodent models, on adding these oligosaccharides in the diet at around 5-10% (wt/wt). [5][6][7][8][9][30][31][32] The dose of FOS at 3% in the present study seems insufficient to exert an anorexic effect in the diet-induced obesity model. In contrast, DFA III at 3% in the diet is effective in preventing excess energy intake.…”
Section: After 2 Weekscontrasting
confidence: 60%
“…The effect of dietary protein and fiber combinations on weight loss is inconsistent, with one study reporting weight and fat loss with a combination of casein or pea protein (40% kcal) and pectin (10% w/w) in DIO rats , whereas another study failed to detect weight loss with casein (29% kcal) and inulin (9% w/w) in genetically obese (JCR:LA‐cp) rats . Here, we demonstrate that diets containing lactalbumin alone or in combination with inulin at both low and high doses were ineffective for weight loss, but a combination of lactoferrin and inulin at low doses decreased BW, lean mass, and fat mass similar to the summative effects of the individual ingredients, indicative of an additive interaction between lactoferrin and inulin.…”
Section: Discussionmentioning
confidence: 72%
“…However, the interaction of protein and fiber in modulating energy balance is poorly understood. A combination of casein (29% kcal) and inulin (9% w/w) did not produce a greater inhibition of food intake than either ingredient alone in obese JCR:LA‐cp rats , whereas casein (40% kcal) and pectin (10% w/w) resulted in a greater inhibition of food intake than casein alone in DIO rats . Similarly, in normal or overweight humans, though some studies reported that breakfasts with egg protein (10% or 20% kcal) and fiber (1 or 7 g) , or high‐protein, high‐fiber snack bars , decreased food intake at a subsequent meal, other studies failed to detect such differences in EI.…”
Section: Discussionmentioning
confidence: 96%
“…(2017) 18 was probably promoted by increased of satiety. It has been suggested that SCFAs, derived from bacterial fermentation of dietary fibers, stimulate the production and secretion of satiety-related hormones associated with fed or fasted state (GLP-1 and PYY) 46 . In our study taxa of Oscillospira genus and C .…”
Section: Discussionmentioning
confidence: 99%